2019
DOI: 10.2196/14019
|View full text |Cite
|
Sign up to set email alerts
|

Visual Analytic Tools and Techniques in Population Health and Health Services Research: Protocol for a Scoping Review

Abstract: BackgroundVisual analytics (VA) promotes the understanding of data using visual, interactive techniques and using analytic and visual engines. The analytic engine includes machine learning and other automated techniques, whereas common visual outputs include flow maps and spatiotemporal hotspots for studying service gaps and disease distribution. The principal objective of this scoping review is to examine the state of science on VA and the various tools, strategies, and frameworks used in population health an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…The study protocol was previously published, detailing the search strategy and methods [ 21 ]. We primarily followed the Joanna Briggs Institute guidelines on scoping reviews [ 22 ] and the framework by Arksey and O’Malley for conducting scoping reviews [ 23 ], with improvements suggested by Levac et al [ 24 ] and Peters et al [ 25 ] for conceptualizing the population, concepts, and context of the study, especially given the context of a methods-based review.…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was previously published, detailing the search strategy and methods [ 21 ]. We primarily followed the Joanna Briggs Institute guidelines on scoping reviews [ 22 ] and the framework by Arksey and O’Malley for conducting scoping reviews [ 23 ], with improvements suggested by Levac et al [ 24 ] and Peters et al [ 25 ] for conceptualizing the population, concepts, and context of the study, especially given the context of a methods-based review.…”
Section: Methodsmentioning
confidence: 99%
“…A substantial body of literature confirms that KT processes build important bridges between evidence and practice, inter alia through co-creation process and the involvement of all relevant actors, from differing backgrounds [21]. These results build on existing evidence of the literature on data visualization and KT, such as assertions that data visualization's interactive nature allows decision-makers to explore data from various perspectives [22]. Scholars have highlighted how visualizations can help users (e.g.…”
Section: Discussionmentioning
confidence: 58%
“…Scholars have highlighted how visualizations can help users (e.g. policy officers presenting data and information) explore, analyze and communicate results from complex big data in health [22], and can be used to convey a larger story or narrative in a stimulating and more effective way than text alone [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include a cohort clustering analysis using disk-like visualisation in public healthcare [6], and an associative service pattern analysis using grid map visualisation in mental healthcare [7]. However, a lack of understanding, availability, development, and application of visual analytics methods answering complex questions persists in the process of evidence development and decisionmaking [8,9].…”
Section: Introductionmentioning
confidence: 99%